2001
DOI: 10.1111/1469-8986.3810133
|View full text |Cite
|
Sign up to set email alerts
|

Neural sources involved in auditory target detection and novelty processing: An event‐related fMRI study

Abstract: We used event-related functional magnetic resonance imaging (erfMRI) techniques to examine the cerebral sites involved with target detection and novelty processing of auditory stimuli. Consistent with the results from a recent erfMRI study in the visual modality, target processing was associated with activation bilaterally in the anterior superior temporal gyrus, inferior and middle frontal gyrus, inferior and superior parietal lobules, anterior and posterior cingulate, thalamus, caudate, and the amygdala/hipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

25
133
5

Year Published

2001
2001
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 332 publications
(163 citation statements)
references
References 38 publications
25
133
5
Order By: Relevance
“…In the current experiment, an anterior region of right hippocampus responded preferentially to deviant trials, consistent with this role. Two recent studies of neural responses to novel stimuli have found similar activations in hippocampus: Kiehl et al [29] presented novel (low-probability) natural sounds in the context of an auditory target detection task with sine wave tones as the baseline stimuli. In addition to bilateral hippocampal activations, they observed novelty responses in regions of left superior temporal and superior frontal gyrus, right postcentral gyrus, and the medial dorsal nucleus of the thalamus similar to the current study.…”
Section: Resultsmentioning
confidence: 99%
“…In the current experiment, an anterior region of right hippocampus responded preferentially to deviant trials, consistent with this role. Two recent studies of neural responses to novel stimuli have found similar activations in hippocampus: Kiehl et al [29] presented novel (low-probability) natural sounds in the context of an auditory target detection task with sine wave tones as the baseline stimuli. In addition to bilateral hippocampal activations, they observed novelty responses in regions of left superior temporal and superior frontal gyrus, right postcentral gyrus, and the medial dorsal nucleus of the thalamus similar to the current study.…”
Section: Resultsmentioning
confidence: 99%
“…For example, several imaging studies have described activations in DLPFC (superior frontal gyrus, superior frontal sulcus) during auditory spatial localization (Griffiths et al, 1998; Martinkauppi et al, 2000; Weeks et al, 2000; Lipschutz et al, 2002; Lutzenberger et al, 2002; Zatorre et al, 2002; Gaab et al, 2003; Leiberg et al, 2006). Conversely, VLPFC activation (IFG; BA 45,47), has been noted during auditory non-spatial processes, such as listening to melodies, attending pitch/rhythm, determining sound length, word/voice discrimination and auditory working memory (Zatorre et al, 1994, 1998; Platel et al, 1997; Linden et al, 1999; Pedersen et al, 2000; Alain et al, 2001; Kiehl et al, 2001; Muller et al, 2001; Kaiser et al, 2003; Maddock et al, 2003; Arnott et al, 2004; Rämä et al, 2004; Rämä and Courtney, 2005; Kaiser et al, 2009; Koelsch et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…No differences were found when comparing verbal and object oddball targets in the whole brain analysis so these conditions were collapsed and compared to the baseline condition. Consistent with other studies of oddball detection (c.f., Kiehl et al, 2001, 2005; Laurens et al, 2005; Wolf et al, 2008), the group contrast between correct target > control target in the oddball task revealed activation across a large area of the parietal cortex, including the left and right VPC ( Figure 3 ). The peak of activation in the left VPC resided in the supramarginal gyrus (Talairach coordinates: -52, -25, 24; Figure 3A ).…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, there is little support for a strict lateralization of these functions in the VPC. For example, many studies of oddball detection find bilateral responses in the VPC to rare targets (c.f., Kiehl et al, 2001, 2005; Laurens et al, 2005; Wolf et al, 2008). Moreover, an increasing number of studies have found engagement of the left VPC during stimulus-driven capture (Wolf et al, 2008; Weidner et al, 2009; Doricchi et al, 2010).…”
Section: Introductionmentioning
confidence: 99%